Pengaruh Intellectual Capital, Kepemilikan Manajerial, dan Kepemilikan Institusional Terhadap Kinerja Keuangan - Muhammad Wildan Affan; Novitasari Agus Saputri; Akbar Alifiani Prianto (ITB AAS INDONESIA, 2023)
Financial Performance is a general description of the company's financial condition in a certain period. This study aims to determine the effect of intellectual capital, managerial ownership, and institutional ownership on financial performance. The research method used is quantitative method. The object in this study uses non-cyclical consumer companies listed on the Indonesia Stock Exchange and obtained a sample of 57. The sampling technique was carried out by purposive sampling method. The results of the study were analyzed using the Statistical Program for Social Science (SPSS) application with descriptive statistical tests, classical assumption tests, multiple linear regression, hypothesis testing and coefficient of determination tests. The results indicate that intellectual capital has an effect on financial performance. Managerial ownership has no effect on financial performance. Institutional ownership has an effect on financial performance. This means that the higher the intellectual capital and institutional ownership, the ROE will increase. Meanwhile, the smaller the proportion of managerial ownership, the smaller the effect on ROE.